Spatial and demographic disparities in short stature among school children aged 7–18 years: a nation-wide survey in China, 2014. Issue 7 (16th July 2019) - Ma, Jia; Pei, Tao; Dong, Fen; Dong, Yanhui; Yang, Zhaogeng; Chen, Jie; Guo, Sihui; Zhao, Qiuling; Wang, Shunan; Ma, Jun; Zhang, Zhixin
Abstract : Objectives: To identify spatial disparities and demographic characteristics of short stature, we analysed the prevalence of short stature collected in a nationwide health survey. Settings: Data were obtained from the 2014 Chinese National Survey on Students Constitution and Health (a cross-sectional study of China). Participants came from 30 provinces, autonomous regions, and municipalities (except Tibet, Hong Kong, Macao, and Taiwan). Participants: There were 213 795 Han school children between 7 and 18 years old enrolled in our study. All participants were sampled by stratified cluster. Primary and secondary outcome measures: Short stature; Chinese and WHO age-specific and gender-specific height growth references were used for short stature assessment. Results: The age-standardised and age–gender-standardised prevalence of short stature nationwide was 3.70% and 2.69% according to Chinese and WHO growth references, respectively. The short stature prevalence differed significantly among age groups, urban and rural areas, and regions with different socioeconomic development levels (all p<0.0001). The prevalence was 2.23% in urban versus 5.12% in rural areas (p<0.001). The prevalence was 2.60% in developed, 3.72% in intermediately developed, and 4.69% in underdeveloped regions (p<0.0001). These values were all according to China's growth reference, but similar patterns were observed on prevalence based on the WHO reference. The spatial distribution of prevalence of short stature presented a clustered pattern. Moran's I value was 0.474 (p < 0.001) and 0.478 (p < 0.001) according to the Chinese and WHO growth references, respectively. The southwest part of China showed a higher prevalence of short stature, whereas lower prevalence of short stature was observed mainly in the northeast part of China. Conclusions: There is an appreciably high prevalence of short stature in rural, underdeveloped areas of China. There are high prevalence spatial clusters of short stature in southwestern China. This provides corroborating evidence for a tailored strategy on short stature prevention and reduction in special areas.